Hyperforones A–C, benzoyl-migrated [5.3.1]-type polycyclic polyprenylated acylphloroglucinols from Hypericum forrestii. Issue 9 (10th March 2020) - Lu, Wei-Jia; Xu, Wen-Jun; Zhang, Yan-Qiu; Li, Yi-Ran; Zhou, Xin; Li, Qi-Ji; Zhang, Hao; Luo, Jun; Kong, Ling-Yi
Abstract : Unprecedented benzoyl-migrated polycyclic polyprenylated acylphloroglucinols with a unique C-1 H-substituted bicyclo[5.3.1]hendecane framework, hyperforones A–C (1–3 ), were isolated from Hypericum forrestii . Abstract : Three unprecedented benzoyl-migrated polycyclic polyprenylated acylphloroglucinols (PPAPs), hyperforones A–C (1–3 ), were isolated from Hypericum forrestii, together with a new benzoyl-substituted analogue (4 ) of hyperforin. Compounds 1–3 are the first examples of naturally occurring benzoyl-PPAPs with a unique C-1 H-substituted bicyclo[5.3.1]hendecane scaffold. Their structures and absolute configurations were established by HRESIMS, NMR spectroscopy data, electronic circular dichroism (ECD) exciton chirality method, ECD calculations, and gauge-independent atomic orbital (GIAO) NMR calculations with DP4+ analyses. A plausible biosynthetic formation of the benzoyl-migrated C-1 H-substituted bicyclo[5.3.1]hendecane skeleton in 1–3 via a sterically favored hemiketalization/Retro-Claisen cascade was proposed. Bzhyperforin (4 ) showed significant cytotoxicity against MDA-MB-231 cells with an IC50 value of 6.88 ± 1.37 μM.